Development of Project Basic Learning (PBL) In Order To Improve Student Learning Outcomes In Science Currents - Paulus, Kristo; Irsyadiah, Nur (Devotion : Journal of Research and Community Service, 2022)
This study aims to investigate the effect of the Project Basic Learning (PBL) learning model on student learning outcomes in science subjects in class VI SDN Utan Kayu Selatan 01 Jakarta for the 2021/2022 academic year. This research is action research with two rounds. Each cycle consists of four stages, namely design, activity and observation, reflection, and revision. The target of this research is the students of class VI SDN that the student learning outcomes have increased from cycle I to cycle II, namely, cycle I (51%) and cycle II (89%). This study concludes that the Project Basic Learning (PBL) learning model has a positive effect on the learning outcomes of students at SDN Utan Kayu Selatan 01, East Jakarta, and this learning model can be used as an alternative to learning science